Stunting Data Warehouse Modeling for Dashboards at the P2KBP3A Office - Tohir, Arik Sofan; Suryono, Suryono; Susiloningtyas, Luluk; Cahyono, Aris Dwi; Zeho, Fannidya Hamdani (Generation Journal, 2025)
The P2KBP3A Office of Kediri Regency is one of the agencies that handles stunting issues. To collect data on children under two years of age (baduta) in each village, this agency is assisted by cadres in each region. The data that has been collected certainly needs to be processed in order to produce information that is useful for decision makers in determining policies. Processing large amounts of data requires data warehouse technology as one of the solutions. In designing this data warehouse, the Nine Step Kimball method with the Star Schema diagram model was used. With this data warehouse, information on the number of stunting cases in each area can be obtained, starting from the sub-district level, village, to hamlet. Additionally, data can also be viewed based on the target and the status of that target, whether it is normal, stunted, wasted, stunted and wasted, or pre-stunted